Printed electronic on flexible and glass substrates - Futera, Konrad Michał; Jakubowska, Małgorzata (Photonics Letters of Poland, 2010)
Organic electronics is a platform technology that enables multiple applications based on organic electronics but varied in specifications. Organic electronics is based on the combination of new materials and cost-effective, large area production processes that provide new fields of application. Being characterized by size, weight, flexibility and environmental friendliness, organic electronics enables low cost production of numerous electrical components and provides for such promising fields of application as: intelligent packaging, low cost RFID, flexible solar cells, disposable diagnostic devices or games, and printed batteries. The paper presents technology of manufacturing electronic elements on flexible and glass substrates. Fabricated structures were characterized form the point of shape, surface and geometry. A variety of substrates were investigated, within some, low cost, non-specialized substrate, designed for other purposes than organic electronics. Results of substrates influence on printing process are described in the present paper. Full Text: PDF References White Paper "OE-A Roadmap for Organic and Printed Electronics". Organic Electronic Association, 2008 MicorDrop datasheet: www.microdrop.de W. Schmidt, F. Schoeller, Service GmbH & Co. KG, Paper Based Substrates for Printed Electronics, Large-area, Organic & Printed Electronics ? Convention (LOPE-C), June 23-25, 2009, Frankfurt, Germany. V. Subramanian, Printed Zinc Oxide Based Electronics: Materials, Devices and Outlook, Large-area, Organic & Printed Electronics ?Convention (LOPE-C), June 23-25, 2009, Frankfurt, Germany